PENGARUH PEMBERDAYAAN KARYAWAN DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL SEKRETARIAT PERUSAHAAN DAERAH PASAR KOTA DENPASAR - Fitriah, Fitriah; Sudibya, I Gede Adnyana (E-Jurnal Manajemen; Vol 4 No 11 (2015), 2015)
This research is influence of employe empowerment and job satisfacation to organizational commitm.. This research was conducted at Sekretariat Perusahaan Daerah Pasar Kota Denpasar di Jalan Sulawesi No 1 Lantai IV Pasar Badung. The respondents were 55 employees who have been propotiance random sampling . Path Analysis is used to test the amount of the contribution that is created from the free variable on the dependent variable . Statistical test tools got the result that the impact of employee empowerment on organizational commitment melaliu employee satisfaction and job satisfaction effect on commitment . ob satisfaction will increase the willingness of an employee to get a better chance to develop creativity , flexibility and autonomy over their own work .
Keywords: Employee empowerment, job satisfaction, organizational commitment